Biomechanical evaluation of a new fixation device for the thoracic spine - Hongo, Michio (Springer-Verlag, 2009)
The technology used in surgery for spinal deformity has progressed rapidly in recent years. Commonly used fixation techniques may include monofilament wires, sublaminar wires and cables, and pedicle screws. Unfortunately, neurological complications can occur with all of these, compromising the patients’ health and quality of life. Recently, an alternative fixation technique using a metal clamp and polyester belt was developed to replace hooks and sublaminar wiring in scoliosis surgery. The goal of this study was to compare the pull-out strength of this new construct with sublaminar wiring, laminar hooks and pedicle screws. Forty thoracic vertebrae from five fresh frozen human thoracic spines (T5–12) were divided into five groups (8 per group), such that BMD values, pedicle diameter, and vertebral levels were equally distributed. They were then potted in polymethylmethacrylate and anchored with metal screws and polyethylene bands. One of five fixation methods was applied to the right side of the vertebra in each group: Pedicle screw, sublaminar belt with clamp, figure-8 belt with clamp, sublaminar wire, or laminar hook. Pull-out strength was then assessed using a custom jig in a servohydraulic tester. The mean failure load of the pedicle screw group was significantly larger than that of the figure-8 clamp (P = 0.001), sublaminar belt (0.0172), and sublaminar wire groups (P = 0.04) with no significant difference in pull-out strength between the latter three constructs. The most common mode of failure was the fracture of the pedicle. BMD was significantly correlated with failure load only in the figure-8 clamp and pedicle screw constructs. Only the pedicle screw had a statistically significant higher failure load than the sublaminar clamp. The sublaminar method of applying the belt and clamp device was superior to the figure-8 method. The sublaminar belt and clamp construct compared favorably to the traditional methods of sublaminar wires and laminar hooks, and should be considered as an alternative fixation device in the thoracic spine.